KEPEMIMPINAN LEMBAGA PENDIDIKAN ISLAM DAN TEKNOLOGI INFORMASI - Rahmatina, Nazeli (Al-Manba, 2018)
The presence of information technology in the 21st century now is one aspect that provides ease as well as challenge itself in an educational institution, not least in Islamic educational institutions. This leads to a demand for leaders of Islamic educational institutions to have competencies not only in leadership skills and skills but also to master science and information technology in improving the quality of learning and school/madrasah management. To advance the Islamic educational institutions, the Leader of Islamic educational institutions must have a vision, learning to evaluation in accordance with the demands of the era of technology. So that the leader of Islamic educational institutions have the skills in applying information technology both in technical operations and in dividing the tasks of educators and education.